KERJASAMA GURU BK DENGAN ORANGTUA DALAM MENANGGULANGI KENAKALAN SISWA (STUDI KASUS DI MTS NW AIK AMPAT) - wijaya, firad; Hamzanwadi (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
The things studied in this research are how the cooperation and efforts of guidance counselors with parents in addressing student delinquency at MTs NW Aik Ampat are implemented, as well as what factors hinder and support the implementation of cooperation to address student delinquency at MTs NW Aik Ampat. The aim of this research is to find ways to tackle student delinquency at MTs NW Aik Ampat and to understand the factors that hinder and support the cooperation between guidance counselors and parents in fostering the religious character of students at MTs NW Aik Ampat. This type of research is field research that is descriptive and qualitative, taking place in MTs NW Aik Ampat. Data collection was conducted using observation, interviews, and documentation methods, with data analysis conducted by the researcher using Mathew Miles's theory: the first step is data reduction, followed by data presentation and conclusion drawing. The research results indicate that: (1) The forms of cooperation between guidance and counseling teachers and parents in addressing student delinquency include the habituation of prayer, reading the Al-Qur’an, daily prayers, healthy and clean living, handshaking and greeting, dressing neatly, and memorizing short verses. (2) The factors that hinder cooperation between guidance and counseling teachers and parents at MTs NW Aik Ampat include the inconsistency of the coordinator from the teacher's side, differences in behavior among students, family background, and influencing technology. (3) Supporting factors include full support from school members and the availability of complete facilities.